Pemenuhan Hak Anak Korban Pornografi Dalam Sistem Peradilan Pidana Anak - Wakim, Paramitha Agustina Grace; Adam, Sherly; Taufik, Iqbal (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: The fulfillment of the rights of child pornography victims is contained in the Child Criminal Justice System Act and Based on the context of Law No. 35 of 2014 on Amendments to Law No. 23 of 2002 on Child Protection and Government Regulation (PP) Number. 40 Year 2011 On The Development, Mentoring and Recovery of Children Victims and Perpetrators Ponography. Legal protection of children and their rights as victims and perpetrators of pornography do not seem to have received serious attention even though it actually depends on how a country finds a leader who cares about children.Purposes of the Research: This paper aims to analyze and discuss the fulfillment of the rights of child pornography victims in the Child Criminal Justice System.Methods of the Research: Research methods are used with normative juridical research types. The problem approach used is the legal approach, concept analysis approach, case approach, Source of legal materials used primary legal materials and secondary legal materials. Collection techniques through literature studies and then analyzed through the way of description using qualitative methods.Results of the Research: The results showed that the fulfillment of the rights of child pornography victims has not been fulfilled properly in accordance with Law No. 11 of 2012 on the Criminal Justice System of Children. This means that the Child Protection Act has not been balanced with the implementation of child protection. This is because there are still obstacles faced in the fulfillment of the rights of children victims porngrafi. The fulfillment of the rights of children victims of pornography in the legislation include: the right of mentoring, the right of health services, the right of guidance, the right of protection and in Government Regulation No. 40 of 2011 on the guidance, mentoring, and recovery of children who are victims and perpetrators of pornography according to Article 20 is done by means of mentoring: counseling, psychological therapy, social advocacy, improving ability and willingness, providing access to health services and / or legal assistance.